PERAN KONFLIK RUSIA-UKRAINA TERHADAP KINERJA KEUANGAN PERUSAHAAN TAMBANG SUB-SEKTOR MIGAS DAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mochammad Ilham (2023)
This research is a quantitative study that aims to find out about the condition of financial performance of oil, gas, and coal companies in Indonesia that listed on Indonesia Stock Exchange and do some comparation between before the conflict of Russia-Ukraine and after the conflict. This research is using three variables such as, return on asset, debt to equity ratio, and earning per share. There are 19 companies in total on this research that can be used as research sample after applying the purposive sample method. Hypotesis testing was carried out using STATA with Wilcoxon-rank test with level of significance by 5%. The results of the test obtained, 1) there are significant difference between return on asset before the conflict and after the conflict, 2) there are no significant difference between debt to equity ratio before the conflict and after the conflict, and 3) there are significant difference between earning per share before the conflict and after the conflict.